Russia's foreign policy change and continuity in national identity - Tsygankov, Andrei P. (Rowman & Littlefield Lanham, 2016)
Now fully updated and revised, this clear and comprehensive text explores the past quarter-century of Soviet/Russian international relations, comparing foreign policy formation under Gorbachev, Yeltsin, Putin, and Medvedev. Challenging conventional views of Moscow?s foreign policy, Andrei P. Tsygankov shows that definitions of national interest depend on visions of national identity and is rooted both in history and domestic politics. Yet the author also highlights the role of the external environment in affecting the balance of power among competing domestic groups.
Includes bibliographical references and index.
Keywords: Great powers